Plasmonic nanoparticle-based epoxy photocuring: A deeper look. (July 2019) - Roberts, Adam T.; Yang, Jian; Reish, Matthew E.; Alabastri, Alessandro; Halas, Naomi J.; Nordlander, Peter; Everitt, Henry O.
Graphical abstract: Abstract: Many epoxy adhesives require high temperatures to bond composite materials. However, oven heating severely restricts what may be attached or enclosed within composite material-based structures and greatly limits the possibilities for repair. Inspired by initial reports of photothermal epoxy curing using plasmonic nanoparticles, we examine how laser-illuminated Au nanoparticles embedded within high-temperature epoxy films convert the conventional thermal curing process into a photothermally driven one. Our theoretical investigations reveal that plasmonic nanoparticle-based epoxy photocuring proceeds through a four-stage process: a rapid, plasmon-induced temperature increase, a slow localized initialization of the curing chemistry that increases the optical absorption of the epoxy film, a subsequent temperature increase as the epoxy absorbs the laser radiation directly, and a final stage that completes the chemical transformation of the epoxy film to its cured state. Our experimental studies validate this model, and also reveal that highly local photocuring can create a stronger bond between composite materials than thermal curing without nanoparticles, at times even stronger than the composite material itself, substantially reducing the time needed for the curing process. Our findings support key advances in our understanding of this approach to the rapid, highly efficient bonding and repair of composite materials.